Zn Doping Effect on the Performance of Fe-Based Catalysts for the Hydrogenation of CO2 to Light Hydrocarbons - Nikolay Dmitrievich Evdokimenko; Gennady Ivanovich Kapustin; Olga Petrovna Tkachenko; Konstantin Borisovich Kalmykov; Alexander Leonidovich Kustov (Molecules, 2022)
In this work, we studied the role of zinc in the composition of supported iron-containing catalysts for the hydrogenation of CO2. Various variants of incipient wetness impregnation of the support were tested to obtain catalyst samples. The best results are shown for samples synthesized by co-impregnation of the support with a common solution of iron and zinc precursors at the same molar ratio of iron and zinc. Catalyst samples were analyzed by various methods: Raman, DRIFT-CO, TPR-H2, XPS, and UV/Vis. The introduction of zinc leads to the formation of a mixed ZnFe2O4 phase. In this case, the activation of the catalyst proceeds through the stage of formation of the metastable wustite phase FeO. The formation of this wustite phase promotes the formation of metallic iron in the composition of the catalyst under the reaction conditions. It is believed that the presence of metallic iron is a necessary step in the formation of iron carbides—that is, active centers for the formation and growth of chain in the hydrocarbons. This leads to an increase in the activity and selectivity of the formation of hydrocarbons in the process of CO2 hydrogenation.